2013
DOI: 10.2166/wh.2013.015
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Legionella strains isolated from environmental samples in Crete, Greece, during the period 2004–2011

Abstract: In Greece, standard tests are performed in watering and cooling systems of hotels. A total of 1,494 water samples were collected during 2004-2011 from 124 hotels from four regions in Crete (Greece). Samples were tested for the presence of Legionella spp.; 103 isolates were identified and typed by polymerase chain reaction (PCR)-sequencing and sequence-based typing (SBT) (in case of L. pneumophila sg 1). Of those, 48 belonged to various serogroups of L. pneumophila (sg 1, 2, 3, 5, 6, 8, 12, 13, and 15), 32 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In Italy, the Lp sg1 distribution rates in the hotel setting differed greatly between two studies, at 27.7% and 55%, including mixed cultures [15,34]. On the other hand, findings from Italy [19], Greece [23], and Turkey [21] have shown that the most frequent colonizers of the hotel water systems in these studies were Lp sg2-14.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In Italy, the Lp sg1 distribution rates in the hotel setting differed greatly between two studies, at 27.7% and 55%, including mixed cultures [15,34]. On the other hand, findings from Italy [19], Greece [23], and Turkey [21] have shown that the most frequent colonizers of the hotel water systems in these studies were Lp sg2-14.…”
Section: Discussionmentioning
confidence: 67%
“…[30]. In another study from Crete, Greece [23], carried out from 2004 to 2011, about 50 non-Lp Legionella spp. were identified in the water systems of the hotel setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of 1559 hotels and accommodation units in Crete with 85,407 rooms and 161,578 beds (data drawn from the Hellenic National Service of Tourism for 2015), could not exclude the island from the presence of TALDs [ 29 ]. The current research was focused mostly on the significance of sampling from recreation areas and spas and in particular from pools, spas, jacuzzis, showers next to swimming pools, shower heads and spa showers.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data for Greece and Europe since 2011 show that the majority of cases were diagnosed with the urine antigen test at a percentage ranging from 82 to 96% and 77 to 82%, respectively (6,(19)(20)(21). Two recent studies in Greece performed environmental detection of Legionella in water distribution systems and molecular typing, but until now no other study in Greece had detected virulence genes (22,23). The objective of this study was to investigate the genetic diversity of L. pneumophila sg2 to sg14 (Lp2-14) in the Greek environment and the existence of virulence genes among them.…”
mentioning
confidence: 99%